Desire and need in architecture - Ibrahim Jawad Kadhim; Ahmed Abed Jalowb (Iraqi Journal of Architecture and Planning, 2018)
Human beings are fundamentally linked to a process of instinct that can make it into a process of research and generation until it becomes sufficient, and then it is renewed in space and another field, and then the process continues without a specific goal. The previous operations are centered on two poles: desire and need for architecture, , As well as the impact of human desire in architecture, they are in a wide space can not be easily understood.The purpose of this research is to identify and integrate this process within the framework of architecture and be specific to reach a goal that satisfies the two processes. Hence, the research problem of (limits of understanding of dialogue of desire and need in architecture) Of the tests and analysis of the results collected. The research found that the architecture seeks to balance the processes of need and desire of therecipient and the user, thus balancing the dual self and the subject in architecture, in which the state of stability can be reached in thought and action.